The Effectiveness of Online-Based Licensing Services at The Capital Investment and Integrated One-Stop Services (DPM-PTSP) in The Fourth Industrial Revolution - Asna Aneta; Erni Soleman; Sukarman Kamuli (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
The research aims to analyze the effectiveness of online-based licensing services at the Capital Investment and Integrated One-stop Services (DPM-PTSP) in the Fourth Industrial Revolution. The research method was using a survey method with an explanatory approach and serving the research findings in a descriptive-quantitative way. The informants were the state civil apparatuses at DPM-PTSP. The data collection techniques were: 1) Observation, 2) Interview, and 3) Questionnaire. Meanwhile, the data analysis techniques used were data reduction, data display, and data verification interpreted quantitatively and qualitatively and taken from primary and secondary data. The research findings were: 1) The integrated one-stop service concept to improve the quality of licensing services in Gorontalo in the Fourth Industrial Revolution; 2) The determinants of the quality of licensing services in Gorontalo in the Fourth Industrial Revolution; 3) The effectiveness of online-based licensing services at DPM-PTSP in terms of a) Services: less optimized online-based licensing service implementation. The evidence argued that the service was ineffective in terms of human resources which were low. Either the staff or facilities and infrastructures were inadequate, b) Online-based program implementation: the implementation of online-based licensing services was not optimized as it was a new program at DPM-PTSP. Besides, several challenges started to appear; such as the limited number of staff who provided the online-based service for the community, the community’s inadequate understanding of how to use the Internet and the online-based licensing services, lack of facilities and infrastructures, and others. The challenges could be reduced by optimizing the education and training for the staff, optimizing socialization from DPM-PTSP to the community who were not experienced in using technology networks, providing facilities and infrastructures needed by providing budget, and optimizing service provision. Furthermore, DPM-PTSP should well respond to the customers’ complaints and improve their service performances.